Pendampingan Digitalisasi Marketing Berbasis Website dan Aplikasi UMKM Klontong di Surabaya - Mochamad Mochklas; Halimatus Sa’diyah; Rudi Irmawanto; Irwansyah; Fasiatun (LPPM Universitas HKBP Nommensen, 2025)
Community service at Klontong UMKM in Surabaya started activities with digital marketing outreach. Next, the Klontong shop will practice marketing strategies through optimizing digital marketing through the marketplace. The aim of this service focuses on assisting the digitalization of marketing based on websites and applications for Klontong UMKM in Surabaya. The expected benefits are that partners are able to adapt and master the applications implemented in service. There are several stages in the implementation method for this service, namely the preparation and socialization stage, training and implementation, and application of technology. Next, a mentoring and evaluation pattern is carried out with the desired service program. The result of dedication is to increase economic independence for Klontong UMKM with marketing techniques that are in line with technological developments. Digital marketing applications make it easier for UMKM grocery stores to reach customers more effectively and widely. The integration between the Warung Kelontong.id website and applications via e-commerce not only increases operational efficiency, but also helps UMKM in analyzing customer data. Keyword: Digital Marketing, Grocery, UMKM, Social Media